Falls from flat roofed house in and around the city of Rewa, Madhya Pradesh: a study from central India - Swarnkar, Manish; Lilhare, Subham (International Journal of Research in Medical Sciences, 2017)
Background: High falls from flat-roofed houses are a common cause of death and disability in this part of central India; the aim of this study was to describe the experience of such falls seen over a 2-year period. Methods: In this cross sectional study one hundred and twenty two patients (96 male and 26 female) who fell from flat roofed houses were entered and analysed. Results: The Prevalence of fall from flat roofed house was 60.3% (122/202). The mean age of the whole group of patients was 16 years (range 1-75 years); majority of cases were of 11-30year age group (54.1%). Males, adolescent and rural population showed a greater tendency to fall from height. The mean height of these accidental falls was 3.65±2:6 m. Head injury was the most common injury and most common cause of mortality and morbidity in these patients. Conclusions: Death due to fall from height is an unforeseen and unfortunate occurrence. Cranio-cerebral trauma is the most common injury in fatal falls from flat roofs. Parental control, guidance and construction of parapet on roof tops can reduce this economic burden and protect vulnerable groups of people of our country from this type of incidents.